Tháng Năm 19, 2024

Rút gọn biểu thức: \(T = \frac{{\left( {\sqrt {2a} – 2\sqrt 2 } \right)\left( {a – 1} \right)}}{{a – \sqrt a – 2}}\left( {a > 0;a \ne 4} \right)\) A \(T = \left( {\sqrt a + 1} \right)\). B \(T = \left( {\sqrt a – 1} \right)\). C \(T = \sqrt 2 \left( {\sqrt a + 1} \right)\). D \(T = \sqrt 2 \left( {\sqrt a – 1} \right)\).

Rút gọn biểu thức: \(T = \frac{{\left( {\sqrt {2a} – 2\sqrt 2 } \right)\left( {a – 1} \right)}}{{a – \sqrt a – 2}}\left( {a > 0;a \ne 4} \right)\)

A \(T = \left( {\sqrt a + 1} \right)\).

B \(T = \left( {\sqrt a – 1} \right)\).

C \(T = \sqrt 2 \left( {\sqrt a + 1} \right)\).

D \(T = \sqrt 2 \left( {\sqrt a – 1} \right)\).

Hướng dẫn Chọn đáp án là: D

Phương pháp giải:

Phân tích tử và mẫu thành nhân tử rồi rút gọn.

Lời giải chi tiết:

\(\begin{array}{l}T = \frac{{\left( {\sqrt {2a} – 2\sqrt 2 } \right)\left( {a – 1} \right)}}{{a – \sqrt a – 2}}\,\,\,\,\left( {a > 0;a \ne 4} \right)\\ = \frac{{\sqrt 2 \left( {\sqrt a – 2} \right)\left( {\sqrt a – 1} \right)\left( {\sqrt a + 1} \right)}}{{\left( {\sqrt a – 2} \right)\left( {\sqrt a + 1} \right)}}\\ = \sqrt 2 \left( {\sqrt a – 1} \right)\end{array}\)

Vậy \(T = \sqrt 2 \left( {\sqrt a – 1} \right)\).